1993
DOI: 10.1152/ajpregu.1993.265.4.r726
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone attenuates hypertension and inhibits growth of renal arteriolar smooth muscle in rats

Abstract: Hypertension is frequently associated with insulin resistance. We evaluated the effects of pioglitazone, an agent that increases insulin sensitivity, on the development of hypertension in the Dahl salt-sensitive (Dahl-S) rat and in the one-kidney, one-clip Sprague-Dawley rat. We also evaluated the effects of pioglitazone on growth of cultured preglomerular renal arteriolar smooth muscle cells. In Dahl-S rats fed a 3% NaCl diet, tail systolic blood pressures and direct arterial pressures were lower (P < 0.05) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 0 publications
1
80
1
Order By: Relevance
“…Dubey et al 55 reported that pioglitazone decreased arterial pressure in Dahl salt-sensitive and renal hypertensive rats but not in normotensive control rats. Pershadsingh and Kurtz 56 demonstrated that ciglitazone improved insulin sensitivity and lowered arterial pressure in obese, insulin-resistant Zucker rats.…”
Section: Interaction Of Hyperinsulinemia Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Dubey et al 55 reported that pioglitazone decreased arterial pressure in Dahl salt-sensitive and renal hypertensive rats but not in normotensive control rats. Pershadsingh and Kurtz 56 demonstrated that ciglitazone improved insulin sensitivity and lowered arterial pressure in obese, insulin-resistant Zucker rats.…”
Section: Interaction Of Hyperinsulinemia Insulinmentioning
confidence: 99%
“…For example, Dubey et al 55 demonstrated that pioglitazone inhibited the mitogenic effect of several growth factors on cultured arteriolar smooth muscle cells. Pershadsingh and Kurtz 56 found that ciglitazone dramatically attenuated the capacity of platelet-derived growth factor to induce sustained increases in intracellular calcium in rat aortic smooth muscle cells.…”
Section: -56mentioning
confidence: 99%
“…Vascular remodeling is now established as a key contributory factor in CVD. In vitro and in vivo studies have shown that thiazolidinediones inhibit the proliferation, hypertrophy, and migration of vascular smooth muscle cells (75)(76)(77). These agents also reduce the progression of intima-media thickness that commonly occurs in patients with atherosclerosis and, in some studies, decreases intima-media thickness per se (78,79).…”
Section: Potential Therapeutic Roles Of Ppar Agonists In Other Vasculmentioning
confidence: 99%
“…As insulin sensitizers these agents could lower blood pressure indirectly by improving insulin resistance [17]. Thiazolidinediones have also been shown to have direct effects on the vasculature [18] and VSMCs [3,19]. It is possible, therefore, that troglitazone and other thiazolidinediones may regulate blood pressure more directly by interfering with the action of growth factors, such as All, involved in the development of hypertension.…”
Section: Referencesmentioning
confidence: 99%